How many routes lead to migration? Comparison of methods to assess and characterize migratory movements. (1st December 2015) - Cagnacci, Francesca; Focardi, Stefano; Ghisla, Anne; van Moorter, Bram; Merrill, Evelyn H.; Gurarie, Eliezer; Heurich, Marco; Mysterud, Atle; Linnell, John; Panzacchi, Manuela; May, Roel; Nygård, Torgeir; et al.
Summary: Decreasing rate of migration in several species as a consequence of climate change and anthropic pressure, together with increasing evidence of space‐use strategies intermediate between residency and complete migration, are very strong motivations to evaluate migration occurrence and features in animal populations. The main goal of this paper was to perform a relative comparison between methods for identifying and characterizing migration at the individual and population level on the basis of animal location data. We classified 104 yearly individual trajectories from five populations of three deer species as migratory or non‐migratory, by means of three methods: seasonal home range overlap, spatio‐temporal separation of seasonal clusters and the Net Squared Displacement (NSD) method. For migratory cases, we also measured timing and distance of migration and residence time on the summer range. Finally, we compared the classification in migration cases across methods and populations. All methods consistently identified migration at the population level, that is, they coherently distinguished between complete or almost complete migratory populations and partially migratory populations. However, in the latter case, methods coherently classified only about 50% of the single cases, that is they classified differently at the individual‐animal level. We therefore infer that the comparison of methods may help point to 'less‐stereotyped' cases in the residency‐to‐migration continuum. For cases consistently classified by all methods, no significant differences were found in migration distance, or residence time on summer ranges. Timing of migration estimated by NSD was earlier than by the other two methods, both for spring and autumn migrations. We suggest three steps to identify improper inferences from migration data and to enhance understanding of intermediate space‐use strategies. We recommend (i) classifying migration behaviours using more than one method, (ii) performing sensitivity analysis on method parameters to identify the extent of the differences and (iii) investigating inconsistently classified cases as these may often be ecologically interesting (i.e. less‐stereotyped migratory behaviours). Abstract : The authors compared three methods to identify migration, drawn from existing definitions of migration and fitted into theoretical frameworks of movement. They consistently classified population as complete or partial migration, but not individual cases of migration. The authors argue that inconsistent classification by methods points to less‐stereotyped behaviours in the residency‐to‐migratory continuum, and put forward the need for an 'index of migratoriness'.